Implementasi Kebijakan Publik Pelaporan Pemerintah Berbasis Akrual (Studi Kasus di Kantor Pelayanan Perbendaharaan Negara Malang) - Widiprana, Rengga Bayu; Ludigdo, Unti; Rosidi, Rosidi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
This study aims to describe the implementation of accrual based reporting policy on LKPP-KPPN Malang with the Policy Implementation Theory of Edward III (1980) as an analytical tool on supporting and inhibiting factors of implementation in internal KPPN Malang. This research uses qualitative research method with case study research model. The results showed that in implementing the policy, KPPN Malang undertook the following steps: preparation (establishment of reconciliation team and LKPP compilers, policy socialization), implementation (report reconciliation, coordination with work unit), measurement (reconciliation of reconciliation balance and internal KPPN ), and reporting (report presentation, report analysis and CALK compilation). The supporting factor of implementation comes from communication and financial resources, while the inhibiting factors come from human resources, equipment resources, dispositions and bureaucratic structures.